2022
DOI: 10.3390/biom12060815
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Cancer Target Ribonucleotide Reductase, Past and Present

Abstract: Ribonucleotide reductase (RR) is an essential multi-subunit enzyme found in all living organisms; it catalyzes the rate-limiting step in dNTP synthesis, namely, the conversion of ribonucleoside diphosphates to deoxyribonucleoside diphosphates. As expression levels of human RR (hRR) are high during cell replication, hRR has long been considered an attractive drug target for a range of proliferative diseases, including cancer. While there are many excellent reviews regarding the structure, function, and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 248 publications
0
16
0
Order By: Relevance
“…RR is a tetramer consisting of two homodimeric subunits. Every subunit contains ribonucleotide reductase regulatory subunit M1 (RRM1) and RRM2 (Bothou 2021, Huff 2022). Jin et al (Jin 2020) found differential enrichment in cell cycle, P53 signaling pathway, DNA replication, apoptosis, and cancer pathways in patients with high expression of RRM2.…”
Section: Discussionmentioning
confidence: 99%
“…RR is a tetramer consisting of two homodimeric subunits. Every subunit contains ribonucleotide reductase regulatory subunit M1 (RRM1) and RRM2 (Bothou 2021, Huff 2022). Jin et al (Jin 2020) found differential enrichment in cell cycle, P53 signaling pathway, DNA replication, apoptosis, and cancer pathways in patients with high expression of RRM2.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] An important proposed mechanism is intracellular Fe binding and inhibition of ribonucleotide reductase via electron transfer to its tyrosine radical. [6,[10][11][12] However, due to drawbacks such as low efficacy and methemoglobinemia, other heterocyclic TSC have been developed since then. [6,13] Further development of Triapine leads, among others, to the di-2-pyridylketone-4,4-dimethyl-thiosemicarbazone (Dp44mT), a widely studied TSC.…”
Section: Introductionmentioning
confidence: 99%
“…Triapine (3‐aminopyridine‐2‐carboxaldehyde thiosemicarbazone) was the first compound of this family to enter clinical trials [8,9] . An important proposed mechanism is intracellular Fe binding and inhibition of ribonucleotide reductase via electron transfer to its tyrosine radical [6,10–12] . However, due to drawbacks such as low efficacy and methemoglobinemia, other heterocyclic TSC have been developed since then [6,13] …”
Section: Introductionmentioning
confidence: 99%
“… Indeed, the most well-known blockbusters like gemcitabine and sofosbuvir contain fluorine atoms on the ribose ring to improve the metabolic stability, the lipophilic character, and lock nucleoside conformations, all of which modulate their pharmacokinetic properties. However, very few organofluorinated group-containing nucleosides were described, with one of the most representative examples being the ribonucleotide reductase inhibitor tezacitabine functionalized by a monofluoro alkene . Furthermore, RNA-type oligonucleotides (ONs) have also rapidly emerged as pivotal molecules in medicinal chemistry as illustrated with the recent mRNA vaccines developed during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%